Active Protection And Monitoring Device For Wireless Chargers - Volek, Radim (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2019)
This thesis deals with the design of monitoring device, which should serve for measurement and recording measured values of wireless charging device. The thesis further solves design of device protection method. Measuring instrument is equipped with several temperature sensors, which measures temperature in selected points of charging device and is also equipped with current sensor, which measures current from power source of charging device. Sensors are connected to development board NXP FRDM-KL27Z with microcontroller MKL27Z64VLH4. Part of this work is also software which serves to evaluation of data obtained by the sensors.
Keywords: wireless charging; active protection system; monitoring system